Prognostic prediction in gastric cancer patients without serosal invasion: comparative study between UICC 7th edition and JCGS 13th edition N-classification systems - Hu, Xiang; Cao, Liang; Yu, Yi (Chinese Journal of Cancer Research; Vol 26, No 5 (October 31, 2014): Chinese Journal of Cancer Research, 2014)
Objective: T-stage and N-stage have been proven to be the most important factors influencing survival in gastric cancer patients, and have been accepted for use in the Japanese Classification of Gastric Carcinoma (JCGC) and the Union International Cancer Control (UICC-TNM) staging systems. The purpose of this study was to compare the prognostic values of the different N classification systems in gastric cancer patients without serosal invasion. Methods: We retrospectively compared the clinicopathological results of 1,115 patients with primary gastric cancer who underwent curative gastric resection. Results: Serosal invasion was identified in 212 of 1,115 patients (19.0%), and it was associated with lymph node metastasis according to the JCGC13th (P